Pengaruh Latihan Jump to Box terhadap Kemampuan Lay Up Shoot Siswa Ekstrakurikuler Basket SMK Negeri 2 Palembang - Bagus Setiawan; Hengki Kumbara; Puput Sekar Sari (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
This research aims to determine the effect of jump to box training on the lay up shoot ability of basketball extracurricular students at SMK NEGERI 2 Palembang. This research uses an experimental method. This research is a quantitative research that uses the "One Group Pretest - Posttest Design" research design method. The sample used is 20 male students. There is one assessment in this research, namely the lay up shoot ability of extracurricular students. basketball. The analysis technique uses the "t-test" method. After carrying out the exercises and carrying out the Posttest, there was an increase in the average of 38.5 from the previous Pretest only getting an average of 27.3, as well as the hypothesis results for the lay up shoot ability of extracurricular basketball students. shows that the calculated t value is greater than the t table, namely 27.5 > 1.73, so Ha is accepted and Ho is rejected, this shows that the jump to box training method has an influence on the results of the lay up shoot ability of basketball extracurricular students at SMK NEGERI 2 Palembang.